Clopidogrel Provides Significantly Greater Inhibition of Platelet Activity Than Aspirin When Combined With Atorvastatin After Coronary Artery Bypass Grafting: A Prospective Randomized Study - AK, KORAY; ARSAN, SİNAN; TETİK, ŞERMİN (SAGE PUBLICATIONS INC, 2010)
Objective: We aimed to compare the effects of 2 different antiplatelet agents on platelet activity in patients receiving atorvastatin after coronary artery bypass grafting (CABG). Methods: We prospectively randomized 50 patients undergoing CABG into 2 groups; group 1 started to receive atorvastatin (10 mg) plus clopidogrel (75 mg; C + A, n = 25) and group 2 atorvastatin (10 mg) and acetylsalicylic acid (ASA; 300 mg, ASA + A, n = 25) daily on postoperative day 1 and continued for 6 months after operation. Adenosine diphosphate (ADP)-induced platelet aggregation and the expressions of glycoprotein (Gp) IIb, GpIIIa, P-selectin, and fibrinogen (Fg) and low-density lipoprotein (LDL) binding to platelets were assessed preoperatively and at postoperative days 7, 90, and 180. Results: The mean age of the patients was 59.6 +/- 7.6 years, and 82% of the patients were males. The combination of C + A markedly inhibited ADP-induced platelet aggregation compared with ASA + A at postoperative days 90 and 180 (52% +/- 6.0% vs 56% +/- 7.25% and 19.6% +/- 3.2% vs 37% +/- 4.1%, P = .039 and P = .0001, respectively). The therapy of C + A significantly suppressed the expressions of GpIIIa at postoperative days 7, 90, and 180 (P = .0001, P = .0001, and P = .0001, respectively) and P-selectin at postoperative days 90 and 180 (P = .035 and P = .002, respectively) when compared to ASA + A. The expression of GpIIb was also significantly depressed at postoperative day 180 in group 1 when compared to group 2 (P = .0001). Low-density lipoprotein binding was significantly increased at day 180 postoperatively in both the groups (basal: 42.9% +/- 5.6% vs 45.3% +/- 4.4% and day 180: 60.3% +/- 4.6% vs 61.8% +/- 5.7%, P = .0001). Conclusions: Our results demonstrate that the combination of C + A is more effective than that of ASA + A in inhibiting ADP-mediated platelet aggregation and expression of major platelet receptors after CABG.
Keywords: coronary artery bypass graft; atorvastatin; clopidogrel; acetylsalicylic acid; platelet aggregation; flow cytometry; THROMBOELASTOGRAPHY; OUTCOMES; STATINS; LIGAND